Mental health status of Francophones and Anglophones living in minority situations in Canada [infographic] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

La santé mentale des francophones et des anglophones vivant en situation minoritaire au Canada [infographie] - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa (2019)

Mortalité dans la minorité francophone au Canada - Une étude de suivi sur 16 ans. La mortalité selon la situation socioéconomique chez les francophones et les anglophones du Canada vivant à l'extérieur du Québec - Sucha, Ewa; Silva, Erika; Batista, Ricardo; Bouchard, Louise (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa, 2014)

Profil santé mentale des communautés francophones en situation minoritaire au Canada. Rapport abrégé - Bouchard, Louise; Dubois, Alejandra; Sucha, Ewa; Colman, Ian (Université d'Ottawa et Institut du Savoir Montfort, 2019)

Les hommes et les femmes francophones en Ontario : un portrait de leur santé - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario et Université d’Ottawa, 2014)

The health of Francophone men and women in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario & University of Ottawa, 2014)

Francophone men and women in Ontario: A health portrait - Bouchard, Louise; Sedigh, Golnaz; Sucha, Ewa; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

Précarité des populations francophones âgées vivant en situation linguistique minoritaire - Bouchard, Louise; Batal, Malek; Imbeault, Pascal; Sedigh, Golnaz; Silva, Erika. E.; Sucha, Ewa (Minorités linguistiques et société, 2015)
Le vieillissement des populations s’est considérablement accentué ces dernières décennies et ce plus particulièrement pour la population francophone vivant en situation linguistique minoritaire au Canada. Nos analyses secondaires de l’Enquête sur la santé des collectivités canadiennes (ESCC) révèlent qu’une grande proportion d’aînés francophones n’a pas de diplôme d’études secondaires et se situe dans le quintile de revenu le plus faible. Des analyses multidimensionnelles des données montrent que les déterminants de la pauvreté tels que le revenu et l’éducation exercent une influence sur la pauvreté des personnes âgées, mais que la langue et l’appartenance à la minorité francophone y contribuent de façon spécifique, ce qui constitue une donnée nouvelle. Mots-clés : vieillissement, minorités linguistiques, personnes âgées, pauvreté, déterminants sociaux de santé

Prevalence and patterns of multimorbidity among linguistic groups of patients receiving home care in Ontario: a retrospective cohort study. - Batista, Ricardo; Reaume, Michael; Roberts, Rihannon; Seale, Emily; Rhodes, Emily; Sucha, Ewa; Pugliese, Michael; Kendall, Claire E.; Bjerre, Lise M.; Bouchard, Louise; Prud'homme, Denis; Manuel, Douglas G.; et al. (BMC Geriatr., 2023)
Background Prior studies have demonstrated the negative impact of language barriers on access, quality, and safety of healthcare, which can lead to health disparities in linguistic minorities. As the population ages, those with multiple chronic diseases will require increasing levels of home care and long-term services. This study described the levels of multimorbidity among recipients of home care in Ontario, Canada by linguistic group. Methods Population-based retrospective cohort of 510,685 adults receiving home care between April 1, 2010, to March 31, 2018, in Ontario, Canada. We estimated and compared prevalence and characteristics of multimorbidity (2 or more chronic diseases) across linguistic groups (Francophones, Anglophones, Allophones). The most common combinations and clustering of chronic diseases were examined. Logistic regression models were used to explore the main predictors of ‘severe’ multimorbidity (defined as the presence of five or more chronic diseases). Results The proportion of home care recipients with multimorbidity and severe multimorbidity was 92% and 44%, respectively. The prevalence of multimorbidity was slightly higher among Allophones (93.6%) than among Anglophones (91.8%) and Francophones (92.4%). However, Francophones had higher rates of cardiovascular and respiratory disease (64.9%) when compared to Anglophones (60.2%) and Allophones (61.5%), while Anglophones had higher rates of cancer (34.2%) when compared to Francophones (25.2%) and Allophones (24.3%). Relative to Anglophones, Allophones were more likely to have severe multimorbidity (adjusted OR = 1.04, [95% CI: 1.02–1.06]). Conclusions The prevalence of multimorbidity among Ontarians receiving home care services is high; especially for whose primary language is a language other than English or French (i.e., Allophones). Understanding differences in the prevalence and characteristics of multimorbidity across linguistic groups will help tailor healthcare services to the unique needs of patients living in minority linguistic situations.